CTNI-46. PIVOTAL STUDY TO EVALUATE SAFETY AND EFFICACY OF EXABLATE MODEL 4000 USING MICROBUBBLE RESONATORS TO TEMPORARILY MEDIATE BLOOD-BRAIN BARRIER DISRUPTION FOR LIQUID BIOPSY IN GLIOBLASTOMA (LIBERATE). (14th November 2022) - Ahluwalia, Manmeet; de Groot, John; Lee, John; Mogilner, Alon; Schwartz, Theodore H; Burns, Terry; Shah, Bhavya; McDermott, Michael; Bettegowda, Chetan; Khosla, Atulya; Sahgal, Arjun; Mishra, Mark; et al.
Abstract: BACKGROUND: Glioblastoma (GBM) has dismal outcome of 14-16 months. One of the challenges of drug development in GBM is lack of requisite circulating-free (cfDNA) in blood samples to develop biomarker driven targeted therapy trials. The Exablate focused ultrasound with circulating microbubble resonators uses the concept of real-time imaging to treat small target spots focusing energy in a non-invasive manner, thereby disrupting the Blood-Brain Barrier (BBBD) with potential to increase cfDNA in blood. METHODS: LIBERATE is a prospective, multi-center, self-controlled pivotal ongoing clinical trial in subjects with suspected GBM evaluating the safety and effectiveness of Exablate Model 4000 to disrupt BBB to achieve a greater proportion of cfDNA in samples taken post-BBB disruption as compared to the sample taken before BBBD. Fifty eligible subjects with suspected GBM who are scheduled to undergo brain tumor resection or biopsy at 10 centers in the U.S. will participate in this study. The primary endpoint is defined for each subject as ratio between his/her cfDNA amount found in the blood sample 1-hour post-BBBD procedure compared to the cfDNA amount found in the blood sample collected pre-BBBD procedure. This study proposes to demonstrate that on average there is at least 2-fold increase in cfDNA (measured by central laboratory) at 1 hour post BBBD. Confirmatory secondary analysis will evaluate correlation between patterns obtained in panel of biomarkers evaluated in the resected tumor tissue and/or biopsy sample and blood sample collected 1-hour post-BBBD. Exploratory endpoints will include: (1) sensitivity of detection of known somatic mutations in the circulating blood samples (circulating tumor DNA) before and after BBBD, (2) time of greatest yield of cfDNA in the samples collected post BBBD blood samples (at 30 min, 1-hour, 2-hour and 3-hour) to determine time of greatest yield, (3) correlation of biomarkers between the imaging and the post-BBBD biomarker samples. (NCT05383872)